Clinical-epidemiological Characterization of Suicide in Elder Adults - Wilfredo Valiente Morejón; Bárbara Junco Sena; Yoel Padrón Vega; Yisel de la Caridad Ramos Águila; Alina Rodríguez Méndez (Revista Finlay)
Foundation: suicide is one of the first causes of death in Pinar del Rio. The mortality rate due to suicide in Consolación del Sur exceeds the national average, most of the cases range over 60 years old. Objective: to characterize elderly people dead due to suicide in Consolación del Sur between 2000 and 2015. Method: a descriptive research was done with the universe of 85 dead elder adults. The calculation was done on the bases of mortality data and typification survey of suicidal behavior of the non-transmissible diseases department of the Provincial Center of Hygiene and Epidemiology. The variables analyzed were: age range, sex, scholarship, marital status, working status, if they lived alone or not, type of conflict, suicidal method, previous suicidal attempt, addictions and premature mortality. Results: the rate of suicide increased proportionally to age, the average age was 73,8 ±8,9 years old. There was a male over mortality of 3,7 men by each woman. The most frequent suicides occurred in old men with elementary school level, without working or marital bond and living with other people but with noticeable problems in the familial structure and functioning. The most frequent method was hanging. Most of the elders did not have previous suicidal attempts nor additions. It was observed a premature death in 52,9 % of the cases. Conclusion: premature death due to suicide can be seen as a reflection of the deterioration of the quantity of life but also its quality of the studied elder adults.